The Directions of Interrelations Between the Company’s Performance and Corporate Social Responsibility (CSR) Activities - Zajkowski, Robert; Domańska, Ada (Acta Universitatis Lodziensis. Folia Oeconomica, 2019)
The interrelations between engagement in CSR activities and the company’s performance are still one of pivotal managerial problems. Ample findings related to this issue seem to reveal a rather hazy than clear picture. In this paper, an attempt has been made to complement this problematic issue with the results of the survey conducted among a group of Polish large and medium‑sized family businesses. The aim of the paper is to analyse relationships between the self‑assessment of the company’s performance and its engagement in various CSR activities. It seems to be interesting to identify what kind of relationship and mutual influences can be found between the company’s economic and non‑economic activities and whether its value aspects, in their broad meaning, exist. To identify this relationship, two groups of linear regression models were adopted (CSR activities or the self‑assessment of the company’s performance as dependent variables). The ultimate conclusion drawn seems to confirm that the problematic area mentioned above should be described rather by a circular than linear direction of influences which were called a multilevel chain of interferences.